Anwar--dream of a dark night / Doordarshan presents ; produced by the Public Service Broadcasting Trust for and in partnership with Prasar Bharati Corporation ; director, research, Anwar Jamal. - Jamal, Anwar; Jamal, Anwar; Chatterjee, Saibal (Open frame, 2009)
The film delves into the theme of achieving big dreams from modest backgrouns. The film explores the tenacity of human spirit, by focusing on how a migrant to Delhi achieves his dream of making a theatre in his village by working a range of lowly and menial jobs.